Innovative development of Kazakhstan: Institutional pradoxes and traps (Journal of Economic Research & Business Administration, 2015)
In article problems of institutional ensuring innovative processes are considered. According to the author, the consistent innovative policy is possible only in case of system legislative, administrative and economic measures of the state for overcoming of arising institutional traps.
Keywords: state financial control; industrial and innovative development; innovations; institutional traps.